2006
DOI: 10.1007/s00125-006-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal programming of hepatocyte nuclear factor 4α in the rat: a key mechanism in the ‘foetal origins of hyperglycaemia’?

Abstract: Aims/hypothesis: Prenatal glucocorticoid exposure causes lifelong hyperglycaemia in rat offspring, associated with permanently increased hepatic phosphoenolpyruvate carboxykinase 2 (PCK2), the rate-controlling enzyme of gluconeogenesis. To elucidate the mechanisms underlying the 'programming' of PCK2, this study examined the effect of prenatal dexamethasone treatment on expression of transcription factors that regulate Pck2. Materials and Methods: Real-time RT-PCR and in situ hybridisation were used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
39
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 41 publications
6
39
2
Order By: Relevance
“…PEPCK is a key regulator of gluconeogenesis and hyperglycemia is a well-known side effect of steroid use. Antenatal DEX treatment has been shown to up-regulate hepatocyte nuclear factor 4 alpha which in turn up-regulates PEPCK gene and this phenomenon has been linked to prenatal foetal programming and hyperglycemia later in life [52].…”
Section: Discussionmentioning
confidence: 99%
“…PEPCK is a key regulator of gluconeogenesis and hyperglycemia is a well-known side effect of steroid use. Antenatal DEX treatment has been shown to up-regulate hepatocyte nuclear factor 4 alpha which in turn up-regulates PEPCK gene and this phenomenon has been linked to prenatal foetal programming and hyperglycemia later in life [52].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Diabetologia, Nyirenda et al [17] report an exciting new potential mechanism for glucocorticoidinduced foetal programming of hyperglycaemia. The authors' previous work demonstrated that exposure to prenatal dexamethasone resulted in persistent upregulation of the mRNA and activity of the cytosolic form of the gluconeogenic enzyme phosphoenolpyruvate carboxykinase (PCK) in adult offspring [18].…”
mentioning
confidence: 99%
“…Furthermore, these changes in PCK expression in adult offspring could not be attributed to altered postnatal maternal behaviour, suggesting that excess foetal glucocorticoid exposure has a permanent effect, programming increased gluconeogenesis [19]. Nyirenda et al [17] have now followed up this work by investigating the effects of supraphysiological levels of glucocorticoids, administered to female rats during the last week of pregnancy, on key hepatic transcription factors known to regulate PCK expression in the rat foetus and adult offspring. Prenatal dexamethasone resulted in an early increase in the transcription of the gene encoding foetal hepatic nuclear factor 4 (Hnf4a), which remained elevated into adulthood, and paralleled the rise in Pck1 expression and hyperglycaemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nyirenda et al present compelling new evidence on the mechanism of fetal programming of gluconeogenesis by glucocorticoid administration during the last third of pregnancy in rats [1], a study that is commented on by McCurdy and Friedman [2]. Nyirenda et al focus on a fluxgenerating enzyme of gluconeogenesis (phosphoenolpyruvate carboxykinase [PCK]) and the factors involved in its transcription, showing how PCK mRNA and that of its controlling transcription factors are localised within the hepatic acinus.…”
mentioning
confidence: 99%